Investing in Sub-Saharan Africa for Growth: Public or Private? - (:unkn) unknown (My University, 2024)
This article examines the relationships between public, private, and economic growth in Sub-Saharan African countries from 1990 to 2019. The study reveals that private investment significantly contributes to long-term economic growth in the region. In contrast, the impact of public investment on long-term growth is not robust. These findings suggest that fostering economic growth in Sub-Saharan Africa requires a shift in policymaking from a public-sector to a private-sector growth approach. Prioritizing the private sector for growth and investment could be advantageous for most countries in the region, given their demographics and the imperative to create job opportunities.
Keywords: African Research